Interpreting Historical Keyboard Music. Sources, Contexts and Performance - Kitchen, John 1950-; Woolley, Andrew (Surrey Ashgate, 2013)
Research in the field of keyboard studies, especially when intimately connected with issues of performance, is often concerned with the immediate working environments and practices of musicians of the past. An important pedagogical tool, the keyboard has served as the workbench of countless musicians over the centuries. In the process it has shaped the ways in which many historical musicians achieved their aspirations and went about meeting creative challenges. In recent decades interest has turned towards a contextualized understanding of creative processes in music, and keyboard studies appears well placed to contribute to the exploration of this wider concern. The nineteen essays collected here encompass the range of research in the field, bringing together contributions from performers, organologists and music historians. Questions relevant to issues of creative practice in various historical contexts, and of interpretative issues faced today, form a guiding thread. Its scope is wide-ranging, with contributions covering the mid-sixteenth to early twentieth century. It is also inclusive, encompassing the diverse range of approaches to the field of contemporary keyboard studies. Collectively the essays form a survey of the ways in which the study of keyboard performance can enrich our understanding of musical life in a given period.Contents: Preface; Introduction; Part I Renaissance Keyboard Music: Some aspects of P-Cug, MM 242: António Carreiras keyboard tentos and fantasias and their close relationship with Jacques Buuss ricercari from his Libro primo (1547), Filipe Mesquita de Oliveira; Making connections: William Byrd, virtual networks and the English keyboard dance, David J. Smith; William Byrds My Ladye Nevells Booke (1591): negotiating between the stile antico and the stile modern in the solo keyboard repertory, Walter Kurt Kreyszig. Part II 17th-Century Keyboard Music: Giovanni Maria Trabaci and the New Manner of Inganni: a musical mockery in the early seicento ricercare, Massimiliano Guido; Places of memory and invention: the compositional process in Frescobaldis manuscripts, Christine Jeanneret; The Libro di Fra Gioseffo da Ravenna: a little light on a 17th-century Italian keyboard collection, Barbara Cipollone; A discourse of styles: contrasting gigue types in the A minor Jig from the Purcell partial autograph, GB-Lbl, MS Mus.1, Terence Charlston. Part III Performance Practice: Questions of keyboard temperament in the 16th century, John Koster; 17th-century harpsichords: playing the four-foot stop, Peter Mole; In playing those bells, his amazing dexterity raised my wonder much higher: carillon performance practice in the 17th and 18th centuries, Carl Van Eyndhoven; Dynamics and orchestral effects in late 18th-century Portuguese organ music: the works of José Marques e Silva (1782-1837) and the organs of António Xavier Machado e Cerveira (1756-1828), João Vaz; Czerny and the organ: pragmatism, prestige and performance practice, Iain Quinn. Part IV Perspectives on 18th-Century Repertoire: Some reflections on François Couperins new and diversified character, Jane Clark; Music for connoisseurs and amateurs: C.P.E. Bach and the keyboard, Susan Wollenberg; João Cordeiro da Silva (1735-1808?): a Portuguese Galant keyboard composer, Mário Marques Trilha. Part V The 19th-Century Piano and Repertoire: Grand and grander: economic sidelights on piano design and piano salesmanship in early 19th-century Vienna, Tilman Skowroneck and Andrew Pinnock; Left-hand techniques in Carl Czernys pedagogical piano works and 19th-century pianism, Katherine Wong; In the footsteps of Jean Paul: sonority and pedalling in Robert Schumanns Papillons, Op. 2, Balder Neergaard; A forgotten repertoire: the emergence of female piano composers in 19th-century Portugal, Nancy Lee Harper; Bibliography; Index.About the Editor: Andrew Woolley is a musicologist and performer with research interests in music of the seventeenth and eighteenth centuries, performance practice, and keyboard music. To date he has published several articles on British and Italian music of the late seventeenth and eighteenth centuries.John Kitchen is a Senior Lecturer in Music, Organist to the University of Edinburgh, and Edinburgh City Organist. He also directs both University and church choirs, gives many solo organ and harpsichord recitals, and is in demand as a continuo player, accompanist, lecturer, writer, adjudicator and reviewer and recording artist.
Some aspects of P-Cug, MM 242 / Filipe Mesquita de Oliveira -- Making connections / David J. Smith -- William Byrd's My Ladye Nevells booke (1591) / Walter Kurt Kreyszig -- Giovanni Maria Trabaci and the new manner of inganni / Massimiliano Guido -- Places of memory and invention / Christine Jeanneret -- The Libro di Fra Gioseffo da Ravenna / Barbara Cipollone -- A discourse of styles / Terence Charlston -- Questions of keyboard temperament in the sixteenth century / John Koster -- Seventeenth-century harpsichords / Peter Mole -- In playing those bells, his amazing dexterity raised my wonder much higher / Carl van Eyndhoven -- Dynamics and orchestral effects in late eighteenth-century Portuguese organ music / João Vaz -- Czerny and the organ / Iain Quinn -- Some reflections on François Couperin's 'new and diversified character' / Jane Clark -- Music for connoisseurs and amateurs / Susan Wollenberg -- João Cordeiro da Silva (1735-1808?) / Mário Marques Trilha -- Grand and grander / Tilman Skowroneck and Andrew Pinnock -- Left hand techniques in Carl Czerny's pedagogical piano works and nineteenth-century pianism / Katherine Wong -- In the footsteps of Jean Paul / Balder Neergaard -- A forgotten repertoire / Nancy Lee Harper.
Includes bibliographical references (pages 271-294) and index.
Keywords: Historically informed performance; Keyboard music; Keyboard instrument; Temperament